PENGARUH KUALITAS PELAYANAN DAN NILAI KONSUMEN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA SALON MORRIN KLATEN - Dyah Afryyanti Wahyu; Sri Isfantin Puji Lestari; Edi Purwanto (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to determine the effect of Service Quality and Consumer Value on Consumer Loyalty with Consumer Satisfaction as an Intervening Variable. This study covers the field of marketing management. The population studied was 137 consumers of Salon Morrin in Klaten. The sample selected using random sampling according to the number of samples set. The number of samples taken in this study was 100 respondents. Data were collected using a personal questionnaire. According to Arianto (2018:83) service quality can be interpreted as focusing on meeting needs and requirements, as well as on timeliness to meet customer expectations. Yazid (2001: 2), the customer value received is the overall consumer assessment of the usefulness of a product based on the perception of what is received and what is given. Danang Sunyoto (2015:140). Consumer satisfaction is one of the reasons why consumers decide to shop at a place. Consumer loyalty is a condition where consumers make consistent repeat purchases and have a positive attitude towards a brand, are committed to the brand and intend to continue their purchases in the future. The data analysis method that will be used in this study is by using a structural equation model (Structural Equation Modeling). SEM offers the ability for path analysis (Path Analytic) (Ghozali, 2015: 39). The path analysis that will be used in this study is Partial Least Squares (PLS), using Smart-PLS 3.0 software. Keywords : Service Quality, Consumer Value, Consumer Loyalty, Consumer Satisfaction